Multimedia Content Analysis - Divakaran, Ajay (Springer, 2017)
Multimedia Content Analysis: Theory and Applications covers the state of the art of multimedia content analysis in a tutorial fashion and provides a plan for future research. It includes unique coverage of multimedia content analysis based products described by pioneers in the field, and provides valuable perspective on the feasibility of state of the art techniques, as well as opportunities for the future. It also addresses the experiential aspect of multimedia content analysis. The material discusses multimedia content analysis in three broad sections, theory, human interaction with multimedia, and commercial products. The theory section reviews multimedia content analysis tools used to derive higher-level semantics from low-level audio and video features and covers the state of the art in temporal video segmentation using unsupervised and supervised techniques. The human interaction section describes techniques for incorporating the human perception of multimedia into analysis. The product section describes the world’s first products based on multimedia content analysis.